2020
DOI: 10.7567/1347-4065/ab5b58
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructural effect on thermoelectric properties in Si films containing iron silicide nanodots

Abstract: Thin film thermoelectric materials have drawn much attention for realizing one-chip stand-alone power sources of Internet of Things devices. Here, we fabricate two types of the nanostructured Si films with high crystallinity: Si films containing β-FeSi 2 nanodots with a wider nanodot size distribution of ∼5-120 nm and Si films containing α-FeSi 2 nanodots with a narrow size distribution of ∼5-20 nm. The thermal conductivity of these films is lower than those of Si-silicide nanocomposite bulks. Interestingly, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Sakane et al 65) revealed hierarchical phonon scattering of FeSi 2 QDs in suppressing k. Two phases of iron silicide QDs were formed in a Si matrix by solid phase epitaxy (SPE) under different temperature and exhibited almost the same PF (∼2650 μW mK −2 at RT), QDs of α-FeSi 2 with a uniform size of ∼5-20 nm was weaker in restricting phonons than that of β-FeSi 2 [Fig. 6(c)], which distributed in a widely hierarchical size of ∼5-120 nm.…”
Section: Low-dimensional Strategies Of Reducing-k-orientedmentioning
confidence: 99%
“…Sakane et al 65) revealed hierarchical phonon scattering of FeSi 2 QDs in suppressing k. Two phases of iron silicide QDs were formed in a Si matrix by solid phase epitaxy (SPE) under different temperature and exhibited almost the same PF (∼2650 μW mK −2 at RT), QDs of α-FeSi 2 with a uniform size of ∼5-20 nm was weaker in restricting phonons than that of β-FeSi 2 [Fig. 6(c)], which distributed in a widely hierarchical size of ∼5-120 nm.…”
Section: Low-dimensional Strategies Of Reducing-k-orientedmentioning
confidence: 99%